Penerapan Metode Arima Box-Jenkins Untuk Peramalan Konsumsi Listrik - Titik Rahmawati; Landung Sudarmana; Agung Priyanto (Politeknosains, 2020)
Electric energy consumption in Indonesia is increasing following the growth of national economy. The rise of activities that need electric energy must be well managed and anticipated. Thus, forecasting of electricity demand in the near future should be considered. One of forecasting methods that has often been used is ARIMA (Autoregressive Integrated Moving Average) time series. This paper aims to explain how to use ARIMA method to forecast electricity energy consumption in a particular area along with its accuracy. The data source supplied to the method is secondary data from PLN (Perusahaan Listrik Negara). For period of 5 years of forecasting, the result shows that the best model of ARIMA method is ARIMA (0,1,0). MAPE (Mean Absolute Percentage Error) value of the model is 0.33%, meaning that the accuracy will be 99.67%.